Sign language interpreting in the Pacific: A snapshot of progress in raising the participation of deaf people. Issue 2 (1st October 2019) - McKee, Rachel; Iseli, Jacqueline; Murray, Angela
AbstractBarriers to acquiring and using a shared sign language alienate deaf children and adults from their fundamental human rights to communication, education, social and economic participation, and access to services. International data collected by the World Federation of the Deaf (WFD) identify that in economically developing countries, deaf individuals are at particularly high risk of marginalization, which applies to countries in the Pacific region. This report provides a snapshot of the status of deaf people as sign language users in six Pacific nations: Fiji, Papua New Guinea (PNG), Samoa, Solomon Islands, Timor Leste and Kiribati. Information was contributed by sign language interpreters from these countries during a panel convened at the first Oceania regional conference of the World Association of Sign Language Interpreters, in Fiji, 2018. The report outlines conditions for education through sign language and the emergence of sign language interpreting as a means of increasing access and social equity for deaf people in these countries, albeit this remains largely on a voluntary basis. While Fiji and PNG governments have recognized the status of sign languages in their respective countries and allocated some resources to the inclusion of sign language users, practical support of deaf sign language users tends to be progressed on grounds of disability rights rather than language rights; e.g., several Pacific countries have ratified the United Nations Convention on the Rights for People with Disabilities, which includes provisions for sign language users, and deaf advocacy efforts have gained political traction from alliance with disability organizations.